Research as a tool for professional medical training - Garmendia Lorena, Fausto (2023)
The training of a medical professional is a truly endless ongoing process. It is based on the axes of ethics, work in the community and research. It includes the stages of general studies, undergraduate and postgraduate, the latter in turn is composed of Continuing Medical Education, Second Specialization, Master's and Doctorate. It is necessary for the doctor to constantly update his knowledge, in order to meet the care needs that patients require, he must also be aware of the creation or discovery of new knowledge and the transmission of the same for adequate training of greater human resources in health, improvement of professional practice, health research and medical education.